An Analysis of Code Switching and Code Mixing Used by Maudy Ayunda on Podcast of CXO Media Channel - Puji Laksono; Santia Dwi Annisa (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2022)
This research is conducted An Analysis of Code Switching and Code Mixing Used by Maudy Ayunda on Podcast of CXO Media Channel. There are two problem statements that the researcher used in this research. (1) what kinds of code switching and code mixing are used by Maudy Ayunda on a Podcast of CXO Media Channel?. (2) what are the social factors influencing code switching and code mixing used by Maudy Ayunda on a Podcast of CXO Media Channel? The researcher used the qualitative method. The researcher used the theory of code switching proposed by by Poplack in Hamers and Blanc (2000) and theory of code mixing proposed by by Muysken (2000). This study also includes the procedures of collecting data and procedure of analyzing data. The result of the study re Extra-Sentential or Tag, Inter-Sentential and Intra-Sentential. Three kinds of code mixing Insertion, Alternation, Congruent Lexicalization. The factors influencing code switching and code mixing are Topic, Participant and Function.